Pembelajaran Kalkulus Berbantuan Sofware Maple: Studi Perbedaan Hasil Kerja Mahasiswa dengan Menggunakan Maple dan Tanpa Menggunakan Maple - Saparwadi, Lalu; Yuwono, Timbul (Universitas Hamzanwadi, 2019)
This study aims to: (1) to find out the results of student work using Maple and without using Maple; (2) to find out how students respond to learning using Maple. This research is qualitative descriptive research. The instruments used in collecting data in this study were tests and non-tests. The results showed that most students were not successful in graphing differential and integral functions without using Maple software. It is different when students use the help of Maple software, all students can successfully graph the differential and integral functions correctly. Differences in the results of student work in completing tasks related to differential calculus and integral calculus also provide benefits, which are very helpful for students in understanding concepts and providing convenience in solving problems of differential calculus and integral calculus.